Hindu Religious Educational Values in the Nanda Tradition of the Pangebekan Ceremony: A Case Study of Agung Petilan Pengerebongan Temple Bali - Komang Sri Surya Hartayanti; I Nyoman Kiriana; I Nyoman Alit Supandi (International Journal of Multidisciplinary Sciences, 2026)
The Nanda Tradition in the Pangebekan Ceremony at Agung Petilan Pengerebongan Temple, Bali is a sacred cultural and religious tradition that has been preserved by the Balinese Hindu community across generations. While previous studies have primarily focused on its ritual, historical, and cultural dimensions, its role as a medium of Hindu religious education has received limited scholarly attention. Therefore, this study aims to analyze the Hindu Religious Education values embedded in the Nanda Tradition and to explain its function in transmitting religious teachings and preserving cultural heritage. This research employed a qualitative approach using a descriptive-analytical method. Data were collected through participatory observation, in-depth interviews, documentation, literature review, and document analysis involving traditional leaders, temple priests, Serati Banten, community leaders, and local community members selected purposively. Data validity was ensured through source and technique triangulation, while data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the Nanda Tradition contains multidimensional Hindu Religious Education values, including religious values reflected in Tri Wisesa and Bhakti Marga Yoga, theological values expressed through devotion to Ida Bhatara Dalem Mutering Jagat Kesiman and Dewa Yajna, ethical values demonstrated through Ngayah and Tri Hita Karana, aesthetic values represented by the Tanda Dance and Gamelan Leluangan, and ecological values reflected in Nyapuh Jagat and Palemahan. The study concludes that the Nanda Tradition functions as an effective medium of religious education that strengthens sradha and bhakti, fosters character development, preserves cultural heritage, and promotes ecological awareness within the Kesiman Traditional Village community.